A logistics book hidden in a linguistics library shelf: a qualitative examination of how resource constraints manifest in library operations - Raphael Aryee; Atia Alpha Alfa (Discover Education)
Abstract Academic libraries are essential to teaching, learning, and national development, making adequate library resources crucial for academic institutions. This study examines how limited library resources, particularly recommended textbooks, affect library operations in Ghanaian public universities. Through semi-structured interviews with eleven undergraduate and postgraduate students, we investigated user behavior and responses to resource scarcity. Using thematic content analysis with NVivo software, we found that limited access to recommended textbooks leads to user frustration, resulting in antisocial behaviors such as hiding, stealing, and damaging books. Based on our findings and existing literature, we present a resource-frustration-user behavior framework that illustrates the relationship between resource limitations and user conduct. This study contributes to understanding how resource constraints manifest in library operations and recommends that library managers increase textbook availability to reduce user frustration. We conclude by suggesting directions for future research in this area.